Perancangan Alat Pengukur Volume Automatic Machine Measuring Of Mass And Dimentionuntuk Pengiriman Barang Dengan Metode Dfma - Syahru ramadonal; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Automatic machine measuring of mass and dimension is a machine that consists of several components that function as retrieval of information in the form of mass (kg) and dimensions (m3) of an object in the form of a regular or irregular (random). The working principle of Automatic machine measuring of mass and dimension is that the camera will take pictures of the light given by the sensor beam (line lacer) which moves together with the camera and by using the triangulation method [7] of the laser and camera, then a broad measurement image can be obtained. from 2D images that will be processed using computer algorithms to get 3D image results to determine the volume of objects,Design forManufacturing assembly is one of systems analysis to assembling components, simultaneously, throughout the products from beginning of process design. As result, obstacles to get assembly could be minimalizing before components production. DFMA analysis will be obtaining the value of efficiency on assembly. Through this way, the efficiency value of machine prototype to separating waste, both, ferromagnetic and non-ferromagnetic materials can be achieved. Furthermore, efficiency value on assembly of prototype design is 2.27% at 3033.75 seconds theoretically. The assembly efficiency value of prototype after production and assembling process on actual condition is 1.67% at 3676,473 seconds. The distinction from these efficiency values is caused by difficulty on assembly of the Arduino Acrylic base and the installation of sub-assembly body cover. As consequences, the time to get assembly will take more time on actual condition rather than theoretically. Keywords:triangulation method,laser,camera,volume, Designing, Design For Manufacturing And Assembly (DFMA), assembly efficiency